Hyperlactatemia in critically ill children: The clinical value of lactate for predicting mortality in the pediatric intensive care unit - Bijay Kumar Meher; Devadarshini Sahoo; Deepti Damayanty Pradhan; Saroj Kumar Satpathy; Alok Satyaprakash Nayak (Wolters Kluwer Medknow Publications, 2018)
Objective: To determine the prevalence of hyperlactatemia among critically ill children and to evaluate the clinical value of lactate levels measured at admission to the pediatric intensive care unit (PICU) to predict mortality. Methods: This prospective observational study was conducted in a tertiary care PICU. 356 critically ill children admitted in PICU were taken for study. Serum lactate level measured at admission, with 306 patients classified in the norm lactatemia group (< 2 mmol/l) and 50 in the hyperlactatemia group (≥ 2 mmol/l). Main outcome measures recorded were Pediatric Risk of Mortality score (PRISM III), predicted mortality score, length of stay in the PICU, need for mechanical ventilation and vasopressor, and death. Results: The prevalence rate of hyperlactatemia was 13.8%, which was associated with an increased length of stay in the PICU, longer duration of mechanical ventilation, increased need for vasopressor, and higher mortality (p<0.05). The following cut-off criteria were predictive of mortality: baseline lactate, >5.42 mmol/l; lactate clearance at 6 h, ≤11.87%; persistent hyperlactatemia at 24 h >3.02 mmol/l; PRISM III score, >10; and predicted mortality score, >5.66. Lactate clearance at 6 h and persistent hyperlactatemia at 24 h had predicted mortality with the highest sensitivity 95% and specificity 100%. Conclusions: A single baseline lactate at admission can predict mortality at admission comparable to PRISM III score. Clearance of lactate at 6 h and hyperlactatemia at 24 h can predict death with the highest sensitivity and specificity.